Examining the significant influence of employees’ participation in decision-making and organizational citizenship behavior on attitude toward work - Barroga, Jean Rachel A.; Quadra, Maricel B.; Reyes, Jesus B.; Bulong, Keith Dimple T.; Pasion, Marlene U. (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2024)
The study investigated the influence of participation in decision-making and organizational citizenship behavior on the attitude toward work. Literature was reviewed to deepen the concept of the study. The study used descriptive assessment and correlational research design. The population of the study were the employees of the institution, and questionnaires were used to gather the data. Weighted mean and Pearson r correlation were applied to analyze the data. The finding indicates that participation in decision-making and organizational citizenship behavior are high. The Pearson r correlation suggests that involvement in decision-making affects the cognitive attitude toward work but not the effective attitude. The same is true with organizational citizenship behavior, the Pearson r correlation indicates no significant correlation.